External Mustarde suture technique in otoplasty revisited: A report of 82 cases. Issue 4 (September 2013) - Eryilmaz, Tolga; Ozmen, Selahattin; Cukurluoglu, Onur; Sezgin, Billur
Abstract In otoplasty surgery the antihelical fold is frequently created using Mustarde sutures. When using the Mustarde suture technique it is important to insert the needle through the cartilage at right angles. This technical objective is easily achieved with an external Mustarde suture technique. A review of 82 patients who underwent otoplasty between 2005 and 2011 was conducted. All patients underwent external Mustarde suture otoplasty without conchal cartilage resection. The cartilage had been softened by rasping and conchomastoidal sutures had been used to correct conchal excess if necessary. In one patient, a secondary revision was performed for inadequate superior pole correction. In three patients sutures were visible after 1 year postoperatively and the sutures were removed under local anaesthesia without any recurrence. In one patient blister formation occurred due to inaccurate packing, but healed without any problem in a few days. No other complications, such as bowstringing of the internal sutures, haematoma, or infection, were observed. The patients expressed a high degree of satisfaction with their results. The risk of technical error is minimal. It is easy to perform and not time-consuming. Due to these advantages, this method is a reliable technique in otoplasty.